2015
DOI: 10.1262/jrd.2014-114
|View full text |Cite
|
Sign up to set email alerts
|

A pre-synchronization program at early postpartum might increase the chances of <i>Bos indicus</i> cows cycling prior to 50 days regardless of the length of calf separation

Abstract: The aim of this study was to establish if pre-synchronization would enhance the number of animals cycling prior to conventional breeding at 45 days irrespective of the length of calf separation. Multiparous Bos indicus cows were allotted in four groups (n = 10). Control group (C) dams remained with their calves; groups G24, G48 and G72, which were partially weaned for 24, 48 and 72 h, respectively, were estrus synchronized using a controlled internal drug. These procedures were performed at 25 days and again a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
12
2
Order By: Relevance
“…This is likely the consequence of the time postpartum when the treatment was applied (Rhodes et al., ). In the present study, almost 20% of the cows did not cycle during the duration of the experimental period; similar results have been reported previously (Mondragón et al., ; Pérez‐Torres et al., ). These animals coincidently experienced FAT losses after parturition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is likely the consequence of the time postpartum when the treatment was applied (Rhodes et al., ). In the present study, almost 20% of the cows did not cycle during the duration of the experimental period; similar results have been reported previously (Mondragón et al., ; Pérez‐Torres et al., ). These animals coincidently experienced FAT losses after parturition.…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports have shown that hormonal treatments prior to 30 days postpartum could enhance the probability of animals becoming pregnant soon after calving either using artificial insemination (Mondragón, Galina, Rubio, Corro, & Salmerón, 2016;Pérez-Torres et al, 2015) or natural mating (Lamb et al, 2008). Nonetheless, the variability of the response could be due to fluctuations in the metabolic profile of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of animals starting their cyclicity was 57%. This proportion is low compared to previous reports where values fluctuated between 70 to 92% (Pérez-Torres et al, 2015;Mondragón et al, 2016). On the other hand, 43% of animals did not ovulate.…”
Section: Discussioncontrasting
confidence: 71%
“…On the other hand, 43% of animals did not ovulate. Nonetheless, this percentage is higher than that reported in previous studies where this figure does not exceed 29% (Pérez-Torres et al, 2015). The discrepancies between values could be the result of differences in the high levels of THI that animals were able to tolerate.…”
Section: Discussioncontrasting
confidence: 71%
“…Cows that were nursing calves delayed the resumption of ovarian follicular growth, ovulation and establishment of a normal lifespan CL (Abeygunawardena and Dematawewa, 2004). Reducing the time that the cow nurses a calf by partial or total weaning procedures increases the number of animals that resume ovarian activity and ovulate (Perea et al, 2008;Pinheiro et al, 2009;Perez-Torres et al, 2015). Rhodes et al (2003) reported that treating anestrous cows with progestagen plus estradiol induces estrus response and ovulation in almost 90% of the cows.…”
Section: Discussionmentioning
confidence: 99%